Analysis of English Diphthongs Pronunciation Errors of Senior High School EFL Students - Lubis, Aisyah Inka Putri; Rahmah, Cut Nadia Muji; Br. Perangin-angin, Alemina (Innovative: Journal Of Social Science Research, 2024)
For many students, particularly those learning English as a foreign language, pronunciation emerges as one of the challenges they encounter. Typically, the issue arises from the accent of their first language, as certain languages exhibit variations in comparison to English, including consonants, vowels, word stress, or intonation. The objective of this study was to find out the pronunciation errors in English diphthongs spoken by second-year Senior High School EFL (English as a Foreign Language) students. This is a descriptive qualitative research. The respondents of this research consist of 26 students. The instrument of the research was a pronunciation test of 16 English words containing 8 English diphthongs. The data were collected by directly recording each diphthong pronunciation of the students. This study found that the diphthong /aʊ/ presented the most difficulties for Indonesian students, while diphthong /ɔɪ/ was easier for them to articulate.